ChemInform Abstract: Collective Synthesis of Cladiellins Based on the Gold‐Catalyzed Cascade Reaction of 1, 7‐Diynes. Issue 32 (24th July 2014) - Yue, Guozong; Zhang, Yun; Fang, Lichao; Li, Chuang‐chuang; Luo, Tuoping; Yang, Zhen
Abstract: The Cladiellin family comprises (‐)‐Scelerophytin A (Ia), (‐)‐Scelerophytin B (Ib), (+)‐Deacetylpolyanthellin A (IIa), (+)‐Polyanthellin A (IIb), (+)‐Cladiella‐6Z, 11(17)‐dien‐3‐ol (III), (+)‐Vigulariol (IV), (‐)‐Cladiellisin (Va), (‐)‐Pachycladin C (Vb) and (‐)‐Pachycladin D (VI).